2022
DOI: 10.3390/app121910034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mobility Patterns in Rural Areas of Low Demographic Density through Stated Preference Surveys

Abstract: Within the multiple urban–rural interactions that make up the territorial dynamics, this article addresses and identifies how mobility relations are produced between neighbouring municipalities that share services. The aim of this research is to carry out a diagnosis of the current mobility situation in an area of low population density in order to identify the needs and possible shortcomings in this area. The initial identification of weaknesses is essential in order to propose solutions for rural mobility. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Similar results were reported for rural Spanish towns by Jménez‐Espada et al. [20], who found that the use of e‐bikes and personal mobility vehicles, such as e‐scooters, is not significant, probably also due to higher average age of the population, a characteristics in common to both UK and Spain. However, in the context of potential future for rural mobility, bicycles and scooters are favoured for short trips over cars in Belgium [17], when multigeneration approach is carried out.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results were reported for rural Spanish towns by Jménez‐Espada et al. [20], who found that the use of e‐bikes and personal mobility vehicles, such as e‐scooters, is not significant, probably also due to higher average age of the population, a characteristics in common to both UK and Spain. However, in the context of potential future for rural mobility, bicycles and scooters are favoured for short trips over cars in Belgium [17], when multigeneration approach is carried out.…”
Section: Discussionsupporting
confidence: 86%
“…In Canada, Millward and Spinney [19] combined spatial and temporal analyses from a survey of 1971 households collecting travel activities by matching GPS tracking to geo-reference respondent locations for a 48-h period to study the urban-rural continuum. Similarly, Jménez-Espada et al [20] studied the multiple urban-rural interactions by developing a survey of 296 residents for a small town in Spain and combining the results with open data from public repositories using geographic information system tools. The town is also characterized by the lack of good PT services which led to a modal shift towards private cars and low propensity towards new modes of transport.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether it is visiting health clinics or buying groceries, the shortage of transportation options accommodating reduced mobility and other age-related constraints restricts the independence and social integration of the elderly within the community. The lack of accessible public transport inevitably isolates seniors and disconnects them from vital resources, significantly exacerbating their existing vulnerabilities, One of the most pressing issues aggravating mobility challenges in rural Trenggalek is the scarcity of elderly-friendly public infrastructure, an issue documented in various regions (Bond et al 2017, Jiménez-Espada et al 2022. The absence of pedestrian-centric design features, including paved paths, wheelchair ramps, clearly designated crosswalks, and optimized public transit routes tailored to elderly needs, hampers their ability to maneuver and navigate independently, aligning with the global challenges faced by elderly individuals in terms of accessible infrastructure.…”
Section: Infrastructure and Mobilitymentioning
confidence: 99%
“…), provincial roads and other types of regional roads. Tourism and means of transport, together with their infrastructures, are intrinsically linked, since, without travel, there is no journey [49]. In this way, the means of transport and their means of communication are some of the driving forces that allow tourism to function.…”
Section: Study Areamentioning
confidence: 99%